The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s0029665116003013
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of fatty acid metabolism in different insulin-resistant phenotypes by means of stable isotopes

Abstract: The obese insulin resistant and/or prediabetic state is characterised by systemic lipid overflow, mainly driven by an impaired lipid buffering capacity of adipose tissue, and an impaired capacity of skeletal muscle to increase fat oxidation upon increased supply. This leads to the accumulation of bioactive lipid metabolites in skeletal muscle interfering with insulin sensitivity via various mechanisms. In this review, the contribution of dietary v. endogenous fatty acids to lipid overflow, their extraction or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Indeed, in the different prediabetic phenotypes the state of impaired glucose tolerance may be characterised by more pronounced peripheral or muscle IR, whilst the state of impaired fasting glucose by more pronounced hepatic IR (12) . Consistent with this, we previously showed that skeletal muscle lipid handling was disturbed in the impaired glucose tolerance state, characterised by an impaired postprandial insulin sensitivity, an increased postprandial TAG extraction and a reduced muscle lipid turnover, compared with individuals with impaired fasting glucose (13,14) .…”
Section: The Concept Of Tissue-specific Insulin Resistancesupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, in the different prediabetic phenotypes the state of impaired glucose tolerance may be characterised by more pronounced peripheral or muscle IR, whilst the state of impaired fasting glucose by more pronounced hepatic IR (12) . Consistent with this, we previously showed that skeletal muscle lipid handling was disturbed in the impaired glucose tolerance state, characterised by an impaired postprandial insulin sensitivity, an increased postprandial TAG extraction and a reduced muscle lipid turnover, compared with individuals with impaired fasting glucose (13,14) .…”
Section: The Concept Of Tissue-specific Insulin Resistancesupporting
confidence: 75%
“…From the above it is evident the muscle and liver insulin resistant phenotypes are distinct which subsequently leads to the question whether these phenotypes respond differentially to dietary intervention. The above reported and previously shown disturbances in muscle lipid turnover in individuals with impaired glucose tolerance as compared to individuals with impaired fasting glucose were shown after ingestion of a high fat, high SFA mixed meal (13,14) . There are indications that dietary fat quality may impact muscle lipid handling.…”
Section: Tissue-specific Insulin Resistance: Determinant Of Interventsupporting
confidence: 62%
“…As mentioned earlier, IR can occur in multiple key metabolic organs such as the liver and skeletal muscle. Nevertheless, insulin sensitivity and lipid metabolism may substantially differ between organs within an individual ( 59 ). Moreover, the extent to which IR is present in these distinct organs may vary among individuals.…”
Section: Ectopic Fat and Insulin Resistance: Pathophysiology And Intementioning
confidence: 99%
“…The in vitro hypoglycemic effect of WHPs was investigated by analyzing extracellular glucose consumption in insulin‐resistant HepG2 cells, a human hepatocellular carcinoma cell line with morphology and function similar to those of liver cells. Insulin resistance is a pathological condition highly linked to the consumption of extracellular glucose as a result of reduced insulin receptor sensitivity (Blaak, ; Drouin‐Chartier et al, ). Met was chosen as the positive control for the test as it is widely used in the treatment of diabetes.…”
Section: Resultsmentioning
confidence: 99%